Aktualisasi Manajemen Kreativitas Guru Sekolah Minggu di Masa Pandemi Covid-19 - Daniel Supriyadi (STIPAK Malang, 2021)
During the current covid-19 pandemic, the implementation of worship activities is very limited. One of the worship programs as a means of church education that has a very strong impact is Sunday School. Where currently Sunday school activities are very limited because children are encouraged to reduce direct interaction. So that the lessons that are carried out can only be done online. Therefore, the purpose of writing this article is to describe the role of Sunday school teachers so that they are maximized in teaching. Through the descriptive qualitative method, it can be concluded that the Actualization of the Creative Management of Sunday School Teachers in the Pandemic Mass. First, all parties understand that Sunday school service during the Covid-19 Pandemic is a challenge that must be resolved by all parties. Both Sunday school teachers understand and understand the nature of Creative Sunday school teachers. Because creativity has a very positive impact on children's spiritual and cognitive. So that it is necessary to actualize the management of Sunday School Teacher Creativity, namely: displaying video images, games, and quizzes will make children clearer and understand better what the Sunday school teacher conveys.AbstrakDi masa pandemi Covid-19 saat ini, pelaksanaan kegiatan-kegiatan ibadah sangat dibatasi. Salah satu program ibadah sebagai sarana pendidikan gereja yang sangat terasa dampaknya adalah Sekolah Minggu. Dimana saat ini kegiatan sekolah Minggu sangat terbatas, karena anak-anak dihimbau untuk mengurangi interaksi secara langsung. Sehingga pengajaran-pengajaran yang dilaksankan hanya bisa dilakukan secara daring. Oleh sebab itu tujuan penulisan dalam artikel ini dapat mendeskripsikan peran guru sekolah minggu supaya maksimal dalam mengajar. Melalui metode kualitatif deskriptif dapat disimpilkan bahwa Aktualisasi Manajement Kreatifitas Guru Sekolah Minggu di Massa Pandemi bahwa. Pertama semua pihak mengerti dalam pelayanan sekolah Minggu di Masa Pandemi Covid-19 merupakan tantangan yang harus diselesaikan oleh semua pihak. Kedua para guru sekolah minggu mengerti dan memahami hakikat Guru sekolah minggu yang Berkreatifitas. Sebab kreatifitas sangat berdampak positif bagi kerohanian anak dan kognitif. Sehingga diperlukan aktualisasi management Kreatifitas Guru Sekolah Minggu yaitu: tampilan gambar video, permainan, serta kuis akan membuat anak-anak menjadi lebih jelas dan paham dengan baik tentang materi apa yang disampaikan oleh guru sekolah minggu.